1999
DOI: 10.1002/(sici)1097-4571(1999)50:7<557::aid-asi2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

H.G. Wells's idea of a World Brain: A critical reassessment

Abstract: What exactly are the Wellsian World Brain or World Encyclopaedia ideas to which reference is so often made? What did they mean for Wells? What might they mean for us? This article examines closely what Wells says about them in his book, World Brain (1938), and in a number of works that elaborate what is expressed there. The article discusses aspects of the context within which Wells's conception of a new world encyclopaedia organization was formulated and its role in the main thrust of his thought. The article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…While Teilhard may have been inspired by H.G. Wells' telecommunications superorganism, the 'world brain' (Rayward 1999), little of the actual internet would have appealed to him. In particular, the ersatz noosphere known as the 'blogosphere' would strike Teilhard as a nightmare version of Leibniz's monadology, according to which reality is constructed through a pre-established harmony (i.e.…”
Section: Teilhard De Chardin's Theology 20: the Completion Of Divinementioning
confidence: 99%
“…While Teilhard may have been inspired by H.G. Wells' telecommunications superorganism, the 'world brain' (Rayward 1999), little of the actual internet would have appealed to him. In particular, the ersatz noosphere known as the 'blogosphere' would strike Teilhard as a nightmare version of Leibniz's monadology, according to which reality is constructed through a pre-established harmony (i.e.…”
Section: Teilhard De Chardin's Theology 20: the Completion Of Divinementioning
confidence: 99%
“…In our time, due to the appearance of modern information and communications technologies, universal access has begun to seem like a realisable goal; it has become common to reread the proposals of Otlet, who is considered a key author in order to understand this movement and to establish guidelines, including the documentation and science of information, to allow a more important role for the members of these disciplines (Rayward, 1999). Sadly, scant attention has been paid to other ideas that may have a closer link to present-day phenomena such as the digital library; one author who is infrequently discussed in our circles is H. G. Wells and his World Brain project.…”
Section: Introductionmentioning
confidence: 99%
“…Being aware of the information problem and looking for alternatives to the scientific journal in scholarly communication, Ostwald 31 Rayward showed that Wells' concept of a World Brain and a World Encyclopedia contained a lot of totalitarian thinking. 37 Ostwald was aware of the proximity of his concept of a world brain to dictatorial thinking when he wrote: 'So the total business of science will be regulated through organizational not dictatorial means. 138 It is probably that Wells knew Ostwald Monogesellschaft' in 1905.…”
Section: Introductionmentioning
confidence: 99%